2019
DOI: 10.1249/mss.0000000000001742
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Dropout in Exercise Trials in Older Adults: The Generation 100 Study

Abstract: This is the largest study to identify dropout-predictors in a long-term exercise program in older adults. Our findings provide new and important knowledge about potential risk factors of dropout in long-term exercise programs in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…The low physical functioning and low SE of the subjects were the reasons for the high dropout rate. It has been shown that physical function, exercise habits, and exercise tolerance influenced the physical health of the community residents in the dropout group when compared with the continuous exercise group 42 . The present study included individuals with an SPPB ≤ 9, and it is plausible that low physical function and low SE might have affected the dropouts.…”
Section: Discussionmentioning
confidence: 86%
“…The low physical functioning and low SE of the subjects were the reasons for the high dropout rate. It has been shown that physical function, exercise habits, and exercise tolerance influenced the physical health of the community residents in the dropout group when compared with the continuous exercise group 42 . The present study included individuals with an SPPB ≤ 9, and it is plausible that low physical function and low SE might have affected the dropouts.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, we observed a significant difference in age between the continuation and dropout groups. Increasing age has commonly been reported as a predictor of adherence within the literature [21,33]. However, no significant differences were noted in SPPB scores, rate of weight gain, exercise habits, exercise intervention between the groups.…”
Section: Discussionmentioning
confidence: 76%
“…In a previous study, 36.8% of patients assessed once or twice per year continuously participated in a similar program [9]. In another study, dropout rates from exercise therapy among older adults were 11.0% and 14.9% at 1 and 3 years, respectively [21]. Previous studies have also reported dropout rates of 27.0% and 32.0% among patients with type 2 [22] diabetes and patients undergoing HD on non-dialysis days at home [23], respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…3 However, the rates of dropout from exercise programs are higher in people with lower levels of physical activity and muscle strength. 29 These previous studies suggest the difficulty of applying physical activity interventions to the prevention of sarcopenia. The present study results showed that coffee is associated with SMI independent of physical activity measured by accelerometers.…”
Section: Discussionmentioning
confidence: 99%